2019
DOI: 10.1016/j.cej.2019.06.033
|View full text |Cite
|
Sign up to set email alerts
|

PIV and dynamic LES of the turbulent stream and mixing induced by a V-grooved blade axial agitator

Abstract: The hydrodynamic behavior of a turbulent flow and the mixing characteristics generated by a V-grooved axial impeller inside an agitated tank reactor were investigated both experimentally and numerically. Angle resolved Particle Image Velocimetry (PIV) techniques with an angular displacement Δθ=5° have been applied and two aerodynamic planes along the blades were considered. PIV-based results were compared to those obtained by Large Eddy Simulation (LES), used with the dynamic Smagorinsky-Lilly sub-grid scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Despite the quantitative discrepancies in the data, all the qualitative trends in the timeaveraged variables are in agreement. Furthermore, the quantitative discrepancies between the experiment and LES are similar or lower than the ones reported for example in [2,8] or in [19]. The initial comparison of measured and computed flow dynamics is performed utilizing the spectra of streamwise and spanwise velocity components evaluated in the points p 1 and p 2 depicted in the left hand side of Figure 4 and located at (4, 0, 0) and (4.53, 1.15, 0), respectively.…”
Section: Computational Remarksupporting
confidence: 77%
See 2 more Smart Citations
“…Despite the quantitative discrepancies in the data, all the qualitative trends in the timeaveraged variables are in agreement. Furthermore, the quantitative discrepancies between the experiment and LES are similar or lower than the ones reported for example in [2,8] or in [19]. The initial comparison of measured and computed flow dynamics is performed utilizing the spectra of streamwise and spanwise velocity components evaluated in the points p 1 and p 2 depicted in the left hand side of Figure 4 and located at (4, 0, 0) and (4.53, 1.15, 0), respectively.…”
Section: Computational Remarksupporting
confidence: 77%
“…[2,[4][5][6]. Furthermore, if any analysis of the system dynamics is performed, it is usually limited to the comparison of turbulence spectra as in [7,8]. Such a situation follows from the fact that most existing verification and validation methods for fluid flow simulations are derived for the computationally cheaper and better established Reynolds-averaged Navier-Stokes equations (RANS) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence kinetic energy is an important index to measure the turbulence degree of a fluid; the fluctuating velocities for the turbulent kinetic energy (TKE 39 or k ) were calculated by considering u ′ = u ″, that is, considering the processed fluctuations free from the influence of the periodic motion. TKE is expressed as where and are the average values of the square of the axial and radial pulsation velocities, respectively, and K a represents the average of TKE over the three cross sections.…”
Section: Experimental Setup and Analysis Methodsmentioning
confidence: 99%
“…In addition, for motor blades, inspired by bionics, 160 Zhu and Gao utilized a winged propeller to suppress the generation of tip vortex cavitation (TVC). 45 Also, the simulation results showed that the winglet propeller significantly weakened the strength of the blade tip vortex wake and had a significant effect.…”
Section: Applicationsmentioning
confidence: 99%